Customer relationship management : how to develop and execute a CRM strategy - Pearce, Michael, ....- (New York : Business Express Press, 2021)
The subject of the book is "Customer Relationship Management (CRM)." The target audience is multi-layered:Businesses of all types and sizes from SME's upwards. Board Directors, Senior Managers and middle managers in CRM related functions: IT, Marketing, Sales, Customer Service etc.MBA and masters' students and upper level graduates studying business related degrees.Students or independent learners seeking CRM education or certification through organisations such as AARM (Association for the Advancement of Relationship Marketing).Those pursuing professional qualifications in marketing through international organisations such as the Chartered Institute of Marketing.CRM first entered the business vocabulary in the early 90's; initially as a systems driven technical solution. It has since escalated in importance as system providers increased their market penetration of the business market and, in parallel, CRM's strategic importance gained more traction as it was recognised that CRM was, at its heart, a business model in the pursuit of sustainable profit. This was accentuated by the academic community starting to address the subject in the early 2000's.To-day, it is a universal business topic which has been re-engineered by the online shopping revolution in which the customer is firmly placed at the centre of the business.The current reality, however, is that, for the vast majority of businesses, CRM has not been adopted as a business philosophy and practicing business model. It has not been fully understood and therefore fully embraced and properly implemented. This book is designed to help the reader by stripping CRM down into its component parts under the umbrella of developing and executing a CRM strategy. It delves into and explains the role and relevance of the "C," "R" and "M" in CRM. It is a practical guide but set within a strategic framework. The outage is clear actionable insights and how to go about converting them into delivery. It is written in an
Keywords: Customer relationship management